The neotectonics of the volcanic arc at the latitude of Copahue volcano (38°S), Andes of Neuquén - Rojas Vera, E. (2009)
The Chancho-Co hill is the main positive feature in the caldera del Agrio domain with the only exception of the Copahue volcano. Its development is lin- ked to a series of NE-trending thrusts with a general vergence to the SE, which affects Late Pliocene successions gathered in Las Mellizas Formation. The main topographic break in this fan of reverse faults coincides with the Copahue Fault. This structure uplifted Late Pliocene sequences over younger unconsolidated fluvial and coluvial deposits. The detailed study of these sequences allowed identifying at least two periods of activity for the Copahue Fault. This fault, as well as the other neigh- bor thrusts, cuts the Copahue lavas to the south showing the precise geometry of the Chanchó-Co uplift. Finally, the inver- sion of Paleogene depocenters at depth determined from gravimetric studies is proposed to explain the deeper geometry of the neotectonic structures in the area.